Using the Multicultural Family Support Centers and Adjustment Among Interethnic and Interracial Families in South Korea. Issue 1 (22nd January 2013) - Chung, Grace H.; Yoo, Joan P.
Abstract : The present study proposes a model of using the Multicultural Family Support Centers and adjustment among foreign brides and their interethnicand interracial families in South Korea based on the narratives of 10 foreign brides married to Korean men and 11 service providers who directly interact with these women and their families. The results illustrate how programs offered through Multicultural Family Support Centers serve as a bridge for these families to pass through mistrust and conflict to reach a point of intimacy and unity as a family. Recommendations for the Multicultural Family Support Centers are made.